Detention or Dissent: Judicial Utilization of Public Safety Assessments During Pretrial Detention Hearings in a New Jersey Courtroom - Torres, Luis C. (Criminal justice policy review, 2025)
This study examines how the Public Safety Assessment (PSA), a type of risk assessment tool employed to assist with pretrial decision-making, is utilized during virtual detention hearings in New Jersey. Drawing on observational data from a single courtroom (N = 330), we (a) describe judicial departures from PSA recommendations, (b) employ logistic regression models to assess the factors predicting departures, and (c) explore the reasons provided by judges for departures. The findings show that departures from PSAs are common and that most defendants are either detained or released under the most restrictive monitoring conditions, even in cases involving defendants considered to be lower risk. Moreover, and consistent with focal concerns, factors signaling a defendant’s dangerousness (e.g., current monitoring status and number of alleged offenses) predict departures. Overall, our findings suggest that judicial discretionary power continues to play a role in the courtroom.